Studi Pengaruh Temperatur Kalsinasi dalam Pembentukan Nanomagnetite dengan Metode Green Synthesis Ekstrak Daun Nanas - Putra Parmita, Ade Wahyu Yusariarta; Panji; Dewanto, Hizkia Alpha; Sasongko, Ashadi; Qulub, Fitriyatul; Triana, Yunita; Parmita, Ade Wahyu Yusariarta Putra (SPECTA Journal of Technology, 2023)
In synthesizing Fe3O4 nanoparticles using the green synthesis method by adding FeCl3.6H2O and pineapple leaf extract. Pineapple leaf extract is used as a natural reducing agent which contains hydroxyl and carbonyl, which acts as a reducing agent for the synthesized FeCl3.6H2O. Then after the precipitate is obtained, calcination will be carried out, where the calcination temperature in the synthesis becomes a factor in forming Fe3O4 nanoparticles. Different calcination temperatures of 400°C, 450°C, and 500°C were given to prepare Fe3O4 nanoparticles, with the XRD test results confirming that Fe3O4 nanoparticles were formed. In the SEM-EDX test, the optimum variation is 400°C because the average particle size is 150.23 nm with irregular particle shapes. Then proceed with the SAA results with a surface area of 60.125 m²/g. Nanomagnetite produced by green synthesis of pineapple leaf extract can be used as a removal dyes.